PENINGKATAN PROSES DAN HASIL BELAJAR BAHASA INDONESIA DENGAN MENERAPKAN MODEL DISCOVERY LEARNING PENDEKATAN MIKIR DI KELAS XII IPA 2 SMAN 12 BUNGO - Suparno, Suparno (Jurnal Tunas Pendidikan, 2023)
This research is a classroom action research was conducted to improve the students’ learning processes and students’ achievement in Bahasa Indonesia class by using Discovery learning model with MIKiR approach. This action was conducted in to two cycles, where each cycle was conducted in two meetings. Based on the data, each cycle showed an increase in both learning processes and learning outcomes. The observation results showed that the students becoming more active after the implementation of discovery learning with MIKiR approach. Cycle one was 70% and it was increased to be 87% in cycle two. This increase also occurred in student learning achievement which continued to increase from the pre-cycle to the first cycle and continued to increase in the second cycle. Before the implementation of the action, only 17% of all students passed the KKM. Then, after the implementation of the action, in the first cycle the average student learning outcomes increased. The percentage increased by 39% from the pre-cycle, i.e. 56% of all students got grades that passed the KKM (70). Then, the learning outcomes of students got increased in the second cycle. Based on the test results of students, the percentage was 78% of 23 students.